The Corporate Social Responsibility and Firms’ Financial Performance: Evidence from Financial Sector of Pakistan - Bagh, Tanveer; Khan, Muhammad Asif; Azad, Tahir; Saddique, Shamila; Khan, Muhammad Atif (International Journal of Economics and Financial Issues, 2017)
Competitiveness of financial sector has increased manifold and the issue of corporate social responsibility (CSR) has become an indispensable concern parallel to concentrating on profitability enhancement. Businesses are consider as social units, they have to serve stakeholders, and tend to execute CSR on priority basis and subsequent disclosure as well. Unhealthy CSR policies may cause externalities and eventual relinquished customers. The main purpose of study is to shed light on the impact of corporate social responsibility on financial performance of banking sector of Pakistan, using a sample of 30 commercial banks listed with Pakistan stock exchange (PSX) for the period of 10 years from 2006 to 2015, selected based upon market capitalization. We applied pooled regression models to investigate the impact of CSR on financial performance. Empirical findings signify the robustness of pooled model that documented a positive and significant impact of CSR on ROA, ROE and EPS. This premise holds that CSR has positive and significant impact on FP of selected commercial banks of Pakistan. Based upon key findings, this study postulates CSR phenomenon is consider as an essential growth element and financial performance-boosting tool by banking industry of Pakistan. Eventually, mainstream of the studies on CSR are in context of well-established companies and nations, however, developing nations are least emphasized, thus the findings of this study greatly contribute in body of knowledge as well as offer pivotal implications for policy makers and governance of financial sector. Keywords: Corporate social responsibility (CSR), financial performance, financial sector, Pooled regression JEL Classifications: M14; L25; O16